2012
DOI: 10.1007/s00424-012-1075-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional M3 cholinoreceptors are present in pacemaker and working myocardium of murine heart

Abstract: The presence of M3 cholinoreceptors and their role in mediation of action potential waveform modulation were determined by immunolabeling of receptor proteins and standard microelectrode technique, respectively. The sinoatrial node (SAN), which was determined as a connexin 43 negative area within the intercaval region, the surrounding atrial tissue, and the working ventricular myocardium exhibited labeling of both M3 and M2 receptors. However, the density of M3 and M2 labeling was about twofold higher in the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Stevia reduced the action potential duration, which potentially reduces the likelihood of arrhythmias and may also be linked to the selective activation of cardiac M 2 muscarinic receptor-mediated blockade of intracellular calcium currents. A recent study showed that pilocarpine (a selective muscarinic receptor agonist) caused a marked reduction in APD 50 and APD 90 on mice atrial myocardium and ventricular preparations [40]. Our finding corroborates this report as stevia was found to activate M 2 muscarinic receptors on healthy gastrointestinal tissues.…”
supporting
confidence: 91%
“…Stevia reduced the action potential duration, which potentially reduces the likelihood of arrhythmias and may also be linked to the selective activation of cardiac M 2 muscarinic receptor-mediated blockade of intracellular calcium currents. A recent study showed that pilocarpine (a selective muscarinic receptor agonist) caused a marked reduction in APD 50 and APD 90 on mice atrial myocardium and ventricular preparations [40]. Our finding corroborates this report as stevia was found to activate M 2 muscarinic receptors on healthy gastrointestinal tissues.…”
supporting
confidence: 91%
“…It should be kept in mind that noradrenalin not only stimulates the G s -coupled β 1 –β 3 adrenoceptors but also the G q -coupled α 1 and G i -coupled α 2 adrenoceptors, and that acetylcholine not only stimulates the G i -coupled M 2 -receptor but also the other muscarinic receptors, including the G q -coupled M 3 -receptor, which is functionally present in the murine sinoatrial node (Abramochkin et al, 2012). Adding to this complexity, it has also become clear that GPCR signaling is not a simple linear pathway of receptor, G protein, and effector.…”
Section: Introductionmentioning
confidence: 99%
“…Their activation may influence both the pace-making activity of the SA and AV nodes and the regulation of cardiac muscle contractile activity by shortening action potential duration [13,14]. Abramochkin et al [15] have demonstrated, in the murine heart, that M3 stimulation of the SA node reduces pacemaker activity, consequently, causing HR decrease. Anyway, these effects are very modest when compared with M2response but may play a role in pathological condition such as heart failure, ischemia or atrial fibrillation owing to an increased number of this receptor subtype and to a decrease in M2 receptors; thus, the role of these receptors is therefore not insignificant [16].…”
Section: The Role Of Muscarinic and β Receptors On The Regulation Of mentioning
confidence: 99%